Langage et communication dans les troubles du spectre de l’autisme (Editions de l'Université de Lorraine, 2024)
This book brings together researchers and professionals to explore the linguistic and communication specificities of people with autism spectrum disorder (ASD). Communication and language disturbances are important identification criteria for ASD. Thus, the absence or delay in the establishment of language, like the presence of language particularities during the early years, are often the reason for the first parents consultation. Then, the speech therapy assessment and diagnosis phase of ASD is based on tools and criteria for assessing skills that should be questioned, in view of the diversity of the profiles of the subjects. Finally, the book addresses recent direct intervention protocols tested by health professionals such as speech therapists (alternative communication tools, innovative digital platforms, etc.). Beyond health professionals, education and early childhood professionals will find in this book useful resources for understanding and supporting people with autism.